Penerapan Gagasan Fast Track Legislation Dalam Pembentukan Undang-Undang Di Indonesia Dalam Perspektif Efisiensi Legislasi - Nugroho, Indra Bayu; Zubaba, Bagaz; Arivia, Cinta Tarisa; Sahrin, Alfi (Inicio Legis Fakultas Hukum Universitas Trunojoyo Madura, 2024)
ABSTRAKFast-Track Legislation merupakan konsep legislasi cepat yang telah diterapkan di beberapa negara, konsep ini memungkinkan suatu Undang-Undang di Parlemen untuk dibahas dan disahkan secara lebih cepat dibandingkan dengan Undang-Undang biasa. Dinamika legislasi cepat di Indonesia sebenarnya telah dilaksanakan melalui adanya Perppu, namun sejatinya secara hakikat menggunakan Perppu sebagai legislasi cepat adalah suatu penyimpangan ketatanegaraan karena Perppu digariskan konstitusi untuk merespon adanya kedaruratan, sehingga dibutuh fast-track legislation untuk mengakomodir konsep legislasi cepat di Indonesia. Tujuan dari penelitian ini adalah usulan teoritis penetapan legislasi cepat secara normatif menggunakan metode fast-track legislation. Metode penelitian yang digunakan dalam penulisan artikel ilmiah ini adalah metode penelitian hukum normatif yang menitik beratkan pada adanya studi literatur. Hasil dari penelitian ini adalah konsep fast-track legislation dapat diterapkan dengan mengakomodirnya dalam Undang-Undang tentang pembentukan Peraturan Perundang-Undangan. ABSTRACTSeveral nations have adopted the fast-track legislation concept, also known as fast-track legislation. Compared to regular laws, this idea facilitates the discussion and passage of bills in Parliament more swiftly. The establishment of a Perppu has really allowed Indonesia to execute the dynamics of quick legislation; nevertheless, utilizing a Perppu as fast legislation is essentially a constitutional deviation, as the constitution established the Perppu's response to emergencies Several nations have adopted the fast-track legislation concept, also known as fast-track legislation. Compared to regular laws, this idea facilitates the discussion and passage of bills in Parliament more swiftly. Fast-track legislation is required to accommodate the concept of fast legislation in Indonesia, even though the dynamics of fast legislation have actually been implemented through the existence of a Perppu. In essence, using a Perppu as fast legislation is a constitutional deviation because the Perppu was outlined by the constitution to respond to emergencies. The theoretical suggestion for normative quick legislation establishment through the fast-track legislative approach is the goal of this research. This scientific work was written using a normative legal research method with a literature study focus. The study's conclusion is that the law governing the creation of legislative regulations can incorporate the idea of fast-track legislation.